Excitatory effect of bradykinin on intrinsic neurons of the rat heart. (June 2019) - Arichi, Shiho; Sasaki-Hamada, Sachie; Kadoya, Yuichi; Ogata, Masanori; Ishibashi, Hitoshi
Abstract: The heart receives sympathetic and parasympathetic innervation through the intrinsic cardiac nervous system. Although bradykinin (BK) has negative inotropic and chronotropic properties of cardiac contraction, the direct effect of BK on the intrinsic neural network of the heart is still unclear. In the present study, the effect of BK on the intracardiac ganglion neurons isolated from rats was investigated using the perforated patch-clamp technique. Under current-clamp conditions, application of 0.1 μM BK depolarized the membrane, accompanied by repetitive firing of action potentials. When BK was applied repeatedly, the second responses were considerably less intense than the first application. The BK action was fully inhibited by the B2 receptor antagonist Hoe-140, but not by the B1 receptor antagonist des-Arg 9 -[Leu 8 ]-BK. The BK response was mimicked by the B2 agonist [Hyp 3 ]-BK. The BK-induced depolarization was inhibited by the phospholipase C inhibitor U-73122. BK evoked inward currents under voltage-clamp conditions at a holding potential of −60 mV. Removal of extracellular Ca 2+ markedly increased the BK-induced currents, suggesting an involvement of Ca 2+ -permeable non-selective cation channels. The muscarinic agonist oxotremorine-M (OxoM) also elicited the extracellular Ca 2+ -sensitive cationic currents. The OxoM response did not exhibit rundown with repeated agonist application. The amplitude of current evoked by 1 μM OxoM was comparable to that induced by 0.1 μM BK. Co-application of 0.1 μM BK and 1 μM OxoM elicited the current whose peak amplitude was almost the same as that elicited by OxoM alone, suggesting that BK and OxoM activate same cation channels. BK also reduced the amplitude of M-current, while the M-current inhibitor XE-991 affected neither resting membrane potential nor the BK-induced depolarization. From these results, we suggest that BK regulates excitability of intrinsic cardiac neurons by both an activation of non-selective cation channels and an inhibition of M-type K + channels through B2 receptors. Highlights: Effect of bradykinin on membrane excitability of rat intracardiac ganglion neurons was investigated. Bradykinin excited the ganglion neurons via B2 receptors. The bradykinin response included the activation of phospholipase C. Bradykinin activated cation channels and inhibited M-currents. These results suggest that bradykinin regulates the excitability of cardiac ganglionated nerve plexus.